English Newspapers Availability and Promotion of Literacy in Ugandan Primary Schools - Yandamo, Ado Sanda; Gaji, Zannah Baba (NIU Journal of Humanities, 2017)
The use of the mass media as a teaching instrument in the classroom has increased considerably at all levels in the past few years. Therefore, this study was conducted on English newspapers availability and promotion of literacy in Ugandan primary schools. The objective of the study was to determine the level of English newspapers availability in Ugandan primary schools. When conducting the study, the sample size selected is 93 out of 209 target population of primary five pupils and English teachers of selected primary schools. Therefore, two sets of questionnaires (one for the teachers and the other for the pupils) where administered during the data collection. As a result, the study established that English newspapers meant for younger children are not adequately available in Ugandan primary schools. Therefore, recommendations were made based on the finding that enough English newspapers meant for younger children should be provided in enough quantity in primary schools. However, newspapers should be included among the recommended texts for teaching reading in primary schools. Keywords: Newspapers, availability and literacy promotion.